Making preschool inclusion work strategies for supporting children, teachers, and programs - Richardson-Gibbs, Anne Marie; Klein, M. Diane (Paul H. Brookes Publishing Co., 2014)
This comprehensive textbook gives education professionals a thorough introduction to inclusion supports: evidence-based practices and strategies that help children with disabilities fully participate in preschool classrooms. Practical materials: In-depth case studies and vignettes from both professional and parent perspectives, strategies for adapting curriculum content, disability-specific interventions to keep and use as a reference